Rule Base System Untuk Mendukung Surveillance Epidemi Penyakit Menular di Kota Makassar Menggunakan SMS Gateway - Dimyati (JTRISTE, 2016)
Rule Base System Supporting the Monitoring Outbreaks of Infectious Diseases in Makassar using SMS Gateway. This research aims to produce applications that implement rule-based reasoning method to determine the status of Extraordinary Events (KLB) and support the activities of epidemics of communicable disease surveillance in Makassar. Detection of epidemic outbreaks of infectious disease can be performed using a rule-based system. Rules in this system is built on outbreak detection method with EWMA, CUSUM and Temporal Detection Method by moving percentile. EWMA and CUSUM method used to calculate the threshold value for the occurrence of epidemics of infectious diseases are still in control. Temporal Detection method moving percentile is used to detect deviations of occurrence data above normal. If events over the threshold or above normal, then it is said to have an outbreak. The use of SMS gateway in this system is a technique used to obtain data on the incidence of infectious diseases via SMS. SMS usage is very supportive epidemic occurrence data collection as one infectious disease surveillance activities. Overall the system is able to work faster than the manual system to determine the status of outbreaks. In addition it is able to integrate the activities of collecting, processing, analyzing, interpreting data, and disseminating information in a systematic and sustainable as a series of epidemic disease surveillance activities.